Musical haptics for the listener: Reflections of a design practitioner. Issue 4 (December 2022) - Turchet, Luca
This short essay focuses on the author's reflections as a design practitioner in the emerging field of musical haptics. The reported perspectives relate to the fields of human-computer interaction and music composition and performance. Both ideas and concerns are presented, which are derived from the process of designing, implementing and evaluating hardware and software haptic devices to be used in musical settings with the aim of enriching the listeners' experiences. Finally, some final thoughts and future interventions are proposed.